2022
DOI: 10.1002/cbic.202200269
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Algal Polysaccharide Degradation to Formaldehyde Detoxification

Abstract: Formaldehyde is a toxic metabolite that is formed in large quantities during bacterial utilization of the methoxy sugar 6‐O‐methyl‐d‐galactose, an abundant monosaccharide in the red algal polysaccharide porphyran. Marine bacteria capable of metabolizing porphyran must therefore possess suitable detoxification systems for formaldehyde. We demonstrate here that detoxification of formaldehyde in the marine Flavobacterium Zobellia galactanivorans proceeds via the ribulose monophosphate pathway. Simultaneously, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…An alternative paradigm for nonoxidative C–C bond fragmentation producing formaldehyde as a product can be found in aldolases – these enzymes catalyze reversible addition between a carbonyl and an alcohol to produce a β-hydroxy carbonyl. For example, 3-hexulose-6-phosphate synthetase catalyzes the reversible aldol reaction between formaldehyde and D -5-ribulose 5-phosphate, which may work in tandem with 6-phospho-3-hexuloisomerase to shift the reaction equilibrium ( 37 , 38 ). While most bacterial aldolases are divalent metal dependent, eukaryotic aldolases represent a cofactorless system that utilizes a catalytic lysine to form a covalent Schiff-base conjugate ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…An alternative paradigm for nonoxidative C–C bond fragmentation producing formaldehyde as a product can be found in aldolases – these enzymes catalyze reversible addition between a carbonyl and an alcohol to produce a β-hydroxy carbonyl. For example, 3-hexulose-6-phosphate synthetase catalyzes the reversible aldol reaction between formaldehyde and D -5-ribulose 5-phosphate, which may work in tandem with 6-phospho-3-hexuloisomerase to shift the reaction equilibrium ( 37 , 38 ). While most bacterial aldolases are divalent metal dependent, eukaryotic aldolases represent a cofactorless system that utilizes a catalytic lysine to form a covalent Schiff-base conjugate ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…It can react with free amino and thiol groups of proteins and nucleic acids, leading to protein and DNA damage as well as cross-link formations (Chen et al 2016 ; Shishodia et al 2018 ; Tayri-Wilk et al 2020 ). It has been shown that higher concentrations of formaldehyde can negatively affect the growth of Z. galactanivorans (Brott et al 2022 ). Thus, reduced growth of the ADH knockout strain could be explained by the potential accumulation of formaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…However, this reaction could not be detected. Both organisms harbor other metabolic pathways for the detoxification of formaldehyde (Brott et al 2022 ). For instance, in Z. galactanivorans , the genes encoding the key enzymes of the ribulose monophosphate pathway are upregulated in the presence of porphyran (Brott et al 2022 ), so an accumulation of formaldehyde is unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations